Upaya Pemerintah Desa Mengurangi Angka Pernikahan Dini Melalui Pemberdayaan Organisasi Keagamaan IPNU-IPPNU Desa Jungsemi Kendal - Nurfatoni, Muhamad; Anwar, Khoirul; Rofiq, Wulida Ainur (Prodi Ilmu Hukum, Universitas Teuku Umar, 2024)
The Jungsemi Village Government recognizes the high rate of early marriages as a serious issue that needs to be addressed immediately. To reduce early marriages, the village government collaborates with religious organizations such as IPNU-IPPNU in an effort to provide education to teenagers. This research discusses the factors causing underage marriages in Jungsemi Village, Kendal Regency, their impacts, and the efforts of the village government in collaboration with the religious organization IPNU/IPPNU to address the issue. This research uses a qualitative field method with a phenomenological approach, conducted in Jungsemi Village, Kangkung District, Kendal Regency, focusing on early marriage, through observation, interviews, documentation, and data analysis involving reduction, presentation, verification, and triangulation to ensure validity. The Jungsemi Village Government has implemented various strategic measures to reduce the rate of early marriage, including conducting socialization about the Marriage Law Number 16 of 2019 with support from organizations such as IPNU/IPPNU and PKK. Through this approach, the village government aims to raise public awareness, especially among teenagers, about the importance of adhering to legal regulations. In addition, policies that tighten marriage permits for minors and require marriage dispensations through the court have been implemented to prevent the negative impacts of early marriage on mental, physical, and economic well-being. Support from religious leaders and the community is also a key factor in creating a supportive social environment. With regular evaluations and ongoing commitment, these measures aim not only to reduce the rate of early marriages but also to enhance legal awareness and social welfare in Jungsemi Village.